STUDENT LEARNING OUTCOMES IN BASIC NATURAL COURSES VIEWED FROM THE ASPECT OF ATTITUDES, PRODUCTS, AND SCIENCE PROCESS SKILLS - Muhammad Syazali; Umar Umar (Universitas Labuhanbatu, 2023)
Science learning outcomes that are only seen from one aspect cannot be called mastering science, even though the learning outcomes are good. The purpose of this study was to analyze student learning outcomes in the Basic Natural Sciences course in terms of attitudes, products, and science process skills. This quantitative descriptive research was carried out in the PGSD Study Program on Campus 2, University of Mataram. The sample consisted of 116 5th-semester students who programmed IKD courses. Learning outcome data were collected using the documentation method. Data that has been successfully collected is analyzed descriptively and visualized in the form of tables and figures using Ms. Excel. The findings that we get from the results of the descriptive analysis are that the average student achievement in science is 67.02 with a grade of B, and the interpretation is good. Judging from the visualization results in the form of a histogram, the learning achievement data tended to be between 40.00 and 100.00. As for proportion, the predominant grade was B+ with a frequency and percentage of 34 and 29.30%, respectively. Based on these facts it can be concluded that student learning outcomes in the Basic Natural Sciences course in terms of attitudes, products, and science process skills are in a good category.Keywords: Student learning outcomes, aspects of attitudes, products, and science process skills AbstrakHasil belajar sains yang hanya dilihat dari salah satu aspek belum dapat disebut menguasai sains, walaupun hasil belajar tersebut sudah baik. Tujuan dari penelitian ini adalah menganalisis hasil belajar mahasiswa pada mata kuliah Ilmu Kealamiahan Dasar ditinjau dari aspek sikap, produk dan keterampilan proses sains. Penelitian deskriptif kuantitatif ini dilaksanakan pada Prodi PGSD di kampus 2 Universitas Mataram. Sampel terdiri dari 116 mahasiswa semester 5 yang memprogramkan mata kuliah IKD. Data hasil belajar dikoleksi menggunakan metode dokumentasi. Data yang telah berhasil dikoleksi dianalisis secara deskriptif dan divisualisasi dalam bentuk tabel dan gambar menggunakan Ms. Excel. Temuan yang kami peroleh dari hasil analisis secara deskriptif adalah rata-rata capaian belajar sains mahasiswa sebesar 67.02 dengan grade B, dan interpretasi baik. Ditinjau dari hasil visualisasi dalam bentuk histogram, data capaian belajar tertendensi pada nilai di antara 40.00 dan 100.00. Adapun secara proporsi, grade yang predominan adalah B+ dengan frekuensi dan persentase secara berturut-turut 34 dan 29.30%. Berdasarkan fakta tersebut dapat disimpulkan bahwa hasil belajar mahasiswa pada mata kuliah Ilmu Kealamiahan Dasar ditinjau dari aspek sikap, produk dan keterampilan proses sains berada pada kategori baik.Kata kunci: Hasil belajar mahasiswa, aspek sikap, produk, dan keterampilan proses sains